Animal Welfare: An Overview (Indian Journal of Animal Production and Management, 2024)
Animal welfare encompasses the physical  and psychological well-being of animals, ensuring  they are healthy, comfortable, and free from stress.  This involves providing adequate resources for their  basic needs, such as food, water, shelter, and  healthcare. Assessing animal welfare involves  observing their behaviour and identifying any signs  of distress or abnormal behaviour. Ethologists play  a crucial role in studying and understanding animal  behaviour patterns. While India has made progress  in animal welfare legislation, challenges persist in  enforcement and implementation. The Prevention  of Cruelty to Animals Act of 1960, with subsequent  amendments, provides a legal framework to protect  animal welfare. However, challenges remain in  ensuring its effective implementation. Other  relevant regulations in India focus on transport,  slaughterhouses, environmental protection, and  marketing. To improve animal welfare in India, it is  essential to strengthen existing laws, raise public  awareness, and promote ethical practices in all  aspects of animal care.
Keywords: animal welfare; history; principles; assessment; regulations